1993
DOI: 10.1093/carcin/14.10.2177
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin sensitivity/resistance in UV repair-deficient Chinese hamster ovary cells of complementation groups 1 and 3

Abstract: We assessed the possible role of the human repair genes, ERCC1 and ERCC3, in resistance to cisplatin-induced cytotoxicity. The UV repair-deficient Chinese hamster ovary (CHO) 43:3B [designated ERCC1(-)] cell line and its paired subline 83-J5, which is stably transfected with the human DNA excision repair gene ERCC1 [designated ERCC1(+)], were used in this study. UV repair-deficient CHO 27-1 cells [designated ERCC3(-)] and its paired subline designated 'ERCC3(+)', which is stably transfected with the human DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 0 publications
5
48
0
1
Order By: Relevance
“…Excision repair cross complementation-1 plays a pivotal role in NER pathway, influencing the repair of platinum/ DNA damage because of its adducts recognition and excision ability (Lee et al, 1993). It has been indicated that subjects with lower ERCC-1 levels had lower DNA repair capacity (Rosell et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Excision repair cross complementation-1 plays a pivotal role in NER pathway, influencing the repair of platinum/ DNA damage because of its adducts recognition and excision ability (Lee et al, 1993). It has been indicated that subjects with lower ERCC-1 levels had lower DNA repair capacity (Rosell et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although the NER complex is composed of at least 17 different proteins (Sancar, 1994;Friedberg, 2001), it appears that upregulation of only a few rate-limiting proteins is necessary to increase the excision repair capacity in resistant tumor cells (Reed, 1998). For instance, cisplatin resistance is associated with increases in the excision repair crosscomplementing ERCC1 or ERCC1/ XPF complexes, but not ERCC3 (Lee et al, 1993;Ferry et al, 2000). This finding with ERCC1 is of clinical relevance, as a twofold increase in ERCC1 mRNA levels has been noted in patient's tumors that have become insensitive to cisplatin (Dabholkar et al, 1994).…”
Section: Increase In Dna Damage Repairmentioning
confidence: 99%
“…A test for the presence of a key protein in the excision repair pathway, ERCC1, is in FDA Phase III trials for use as a predictive factor in tailoring chemotherapy to patients with nonsmall cell lung cancer (28). Conversely, increased efficiency of excision repair leads to rapid removal of cisplatin adducts and is associated with cisplatin resistance in human tumor cells (29,30). We used 156-mer DNA probes (Figs.…”
Section: Removal Of Lesions By Excision Repairmentioning
confidence: 99%